FAKTOR YANG MEMPENGARUHI PERILAKU BULLYING PADA REMAJA DI SMP N 1 TELAGA BIRU - Nur Uyuun I. Biahimo; Inne Ariane Gobel; Magvira Yahya (Zaitun (Jurnal Ilmu Kesehatan), 2020)
Bullying is the act of suppressing or intimidating other children both physically and verbally and usually there is an imbalance of power between the perpetrators and victims of bullying. The act of bullying is done by a senior who feels more powerful to his juniors or a person or group of people who feel more powerful to a weaker person. The purpose of this research was to determine the factors that influence bullying behavior in adolescents. The design of this study used a non-experimental cross sectional design. The sampling technique uses purposive sampling with a total sample of 75 students from a total of 293 students. The analysis of this study used the chi square test with a significant α = 0.05, the results showed a family factor relationship to bullying behavior, the results of the chi square test obtained p value = 0.007. The results showed a peer factor correlation with bullying behavior, the chi square test results obtained p value = 0.017. The results showed a correlation of peer environmental factors to bullying behavior, chi square test results obtained p value = 0.017.